2014
DOI: 10.5539/jel.v3n3p108
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing the Active and Collaborative Learning Model in the Introductory Physics Course

Abstract: Model of active and collaborative learning (ACLM) applied in training specific subject makes clear advantage due to the goals of knowledge, skills that students got to develop successful future job. The author exploits the learning management system (LMS) of Hanoi National University of Education (HNUE) to establish a learning environment in the Introductory Physics course Part 2, which supports to the blended learning, for the 1 st year student. The method of pattern languages is taken to redesign learning co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…While most of the aforementioned studies reported the benefits and challenges of the individual dimensions of ABC learning environments or a combination of active and collaborative learning [26] or blended and collaborative learning [27] [28] [25], new challenges may arise when one simultaneously combines the ABC learning environments, making their implementation complex. This may explain the lack of wide-spread development and simultaneous adoption of ABC learning environments in core STEM courses.…”
Section: Benefits and Challenges Of Abc Learning Environmentsmentioning
confidence: 99%
“…While most of the aforementioned studies reported the benefits and challenges of the individual dimensions of ABC learning environments or a combination of active and collaborative learning [26] or blended and collaborative learning [27] [28] [25], new challenges may arise when one simultaneously combines the ABC learning environments, making their implementation complex. This may explain the lack of wide-spread development and simultaneous adoption of ABC learning environments in core STEM courses.…”
Section: Benefits and Challenges Of Abc Learning Environmentsmentioning
confidence: 99%
“…Based on interviews conducted and findings in previous journals, the elements of collaborative learning to identify technology knowledge, pedagogical knowledge and content knowledge of students in enhancing quality and employability skills in the future when they work in industries. According to the data collected and analysed, from the interview sessions, all experts highlighted that collaborative learning is critical to be applied in the class, especially in terms of technologies such as using desktop workspace to produce group projects, using web-based software in designing product, developing projects through internet networks and using digital tools to search information needed like those used in researching [41,42,43]. Moreover, group learning can be used to teach students to become confident in social interaction and communication with other people, to create a discussion group, a forum for sharing information, views and knowledge to build teamwork spirit to control emotions and self-motivation when receiving instructions from tutors and peers [44,45,46].…”
Section: Elements Of Collaborative Learningmentioning
confidence: 99%
“…Students should be encouraged to exchange the ideas and to improve the sample design. The teacher can use various tactics to have the best achievements [42,52,53]. The concern is that students constrained a strong basis or background within any given area for the experiential to strengthen the learning effectiveness [48].…”
Section: Competencies From Subjects Figurementioning
confidence: 99%